The role of government assistance, housing, and employment on postpartum maternal health across income and race: a mixed methods study - Chelsea L. Kracht; Kelsey O. Goynes; Madison Dickey; Briasha Jones; Emerson Simeon; Jada Butler; Maryam Kebbe; Kaja Falkenhain; Emily W. Harville; Elizabeth F. Sutton; Leanne M. Redman (BMC Public Health)
Abstract Background Stressful large-scale events, such as the COVID-19 pandemic and natural disasters, impact birthing individuals’ postpartum experiences and their mental health. Resultant changes in government assistance, housing, and employment may further exacerbate these impacts, with differences experienced by varying income levels and races. This study aimed to examine maternal depression and anxiety in postpartum individuals by income and race during a stressful large-scale event, and the mediating role of government assistance, housing, and employment. Methods An explanatory sequential mixed methods study was conducted (QUANT + QUAL). For aim 1 (quantitative), birthing individuals who delivered during peak pandemic (June 2020 - September 2021) completed questionnaires related to their perinatal experiences and mental health. Macrosystem factors (government assistance, housing, and employment changes) were assessed using the Psychosocial Recommended Measures. The Edinburgh Postnatal Depression Scale (EPDS) and the Generalized Anxiety Disorder-7 (GAD7) assessed depression and anxiety, respectively. Serial linear regression models assessed the relationship between race and income with mental health and macrosystem factors. For aim 2 (qualitative), 40 individuals from the quantitative study balanced by income (low vs. high income) and race (Black vs. White) completed one-on-one semi-structured interviews which were analyzed using thematic analysis. Results Amongst 1582 birthing individuals, Black individuals had a significantly higher EPDS score compared to White counterparts. Not receiving government assistance, unstable housing, and experiencing various employment changes were all related to worse mental health during stressful large-scale events. In semi-structured interviews, low-income individuals discussed that government assistance helped alleviate a financial and mental burden. Low- and high-income individuals reported varying job changes that impacted their mental health (low-income: job loss, high-income: increased hours). Conclusions This research spotlights the negative impact of large-scale events most affected both Black and low-income individuals’ postpartum mental health, and the role of government assistance, stable housing, and secure employment in helping to alleviate these disparities between income levels.